Peran Sentiment Analysis dalam Business Intelligence dan Pengambilan Keputusan Berbasis Data - Achmad Solechan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Rapid growth of digital platforms has generated large volumes of unstructured data, particularly customer reviews, social media comments, and online opinions, which contain valuable insights for organizations. This study aims to examine the role of sentiment analysis in Business Intelligence and data-driven decision-making. The method used is a narrative literature review by analyzing 30 selected journal articles related to sentiment analysis, business intelligence, decision-making, customer reviews, marketing analytics, and data-driven culture. The findings show that sentiment analysis plays an important role in transforming textual data into strategic information that can support customer understanding, marketing decisions, product development, customer relationship management, reputation monitoring, and strategic planning. The integration of sentiment analysis into Business Intelligence enables organizations to not only understand what happens through numerical data, but also why it happens through customer opinions and emotions. However, its implementation still faces challenges related to data quality, informal language, sarcasm, algorithmic bias, model interpretability, and human validation. This study implies that sentiment analysis can strengthen modern Business Intelligence and support more responsive, objective, and evidence-based managerial decision-making.